Globalization and Labor Market Institutions: International Empirical Evidence - Niklas Potrafke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2013)
A widespread concern is that labor market institutions erode in the course of globalization, which, in turn, decreases employment and wages. By using panel data and crosssectional data, I investigate the influence of globalization on labor market regulation. I use the indicators of labor market institutions by Gwartney et al. (2012) and the KOF indices of globalization. To deal with potential reverse causality, I employ a system GMM panel estimator and use a constructed trade share as proposed by Frankel and Romer (1999) as an instrumental variable for globalization in cross sectional models. The results do not show that globalization induced labor market deregulation.
Keywords: F57; F16; J58; J88; 330; Globalization; labor market institutions